Oncolytic Immunotherapy: Conceptual Evolution, Current Strategies, and Future Perspectives - Guo, Zong Sheng; Liu, Zuqiang; Kowalsky, Stacy; Feist, Mathilde; Kalinski, Pawel; Lu, Binfeng; Storkus, Walter J.; Bartlett, David L. (Frontiers in Immunology, 2017)
The concept of oncolytic virus (OV)-mediated cancer therapy has been shifted from an operational virotherapy paradigm to an immunotherapy. OVs often induce immunogenic cancer cell death (ICD) and they may interact directly with immune cells as well, to prime antitumor immunity. We and others have developed a number of strategies to further stimulate anti-tumor immunity and to productively modulate the tumor microenvironment (TME) for potent and sustained anti-tumor immune cell activity. First, OVs have been engineered or combined with other ICD inducers to promote more effective T cell cross-priming and in many cases, the breaking of functional immune tolerance. Secondly, OVs may be armed to express Th1-stimulatory cytokines/chemokines, or co-stimulators to recruit and sustain the potent antitumor immunity into the TME in order to focus their therapeutic activity within sites of disease. Third, combinations of OV with immunomodulatory drugs or antibodies that recondition the TME, have proven to be highly promising in early studies. Fourth, combination of OVs with other immunotherapeutic regimens (such as prime-boost cancer vaccines, CAR T cells; armed with bispecific T-cell engagers) have also yielded promising preliminary findings. Finally, OVs have been combined with immune checkpoint blockade, with robust anti-tumor efficacy being observed in pilot evaluations. Despite some expected hurdles for the rapid translation of OV-based state-of-the-art protocols, we believe a cohort of these novel approaches will join the repertoire of standard cancer treatment options in the near future.